Is the sustainability potential of vertical greening systems deeply rooted? Establishing uniform outlines for environmental impact assessment of VGS. (July 2022) - Rowe, T.; Poppe, J.; Buyle, M.; Belmans, B.; Audenaert, A.
Abstract: Building-related green infrastructures can help reduce several problems associated with urban life. However, while green roofs are reasonably well established and researched, questions remain about the environmental sustainability of vertical greening systems. This article reviews the use of life cycle assessment (LCA) to answer these questions. Methodological choices made in current LCA studies for modeling vertical greening systems are assessed. It is shown that a wide variety in boundary conditions used and assumptions made is prevalent. Based on the lessons learned a framework outline is proposed as a first step towards a more standardized assessment methodology. This outline is built around the life cycle phases and the boundary conditions of vertical greening systems, complemented by case specific data requirements and delivered benefits. The reviewed studies are compared with the framework to identify gaps and opportunities for improvement of current practices. It can be concluded that, to correctly represent the environmental impact of vertical greening systems, the associated benefits need to be better accounted for. For some benefits, i.e., energy savings due to reduced heating/cooling demand, CO2 sequestration, and air pollution reduction, it should be possible to implement them into LCA studies in the short to medium term because basic models and data are available for integration in the state-of-the-art. For other benefits, such as impacts on biodiversity, noise reduction, and psychological and health effects, quantitative data are still lacking, and additional research should be carried out to enable their integration. Highlights: LCA methodologies used for modelling vertical greening systems are explored. Better modelling of the benefits of vertical greening systems in LCA is needed. Standardization is needed to ensure LCA results are comparable between studies.